Role of stressful and traumatic life events in obsessive-compulsive disorder - Fontenelle, Leonardo F.; Cocchi, Luca; Harrison, Ben J.; Miguel, Euripedes C.; Torres, Albina Rodrigues [UNESP] (OMICS International, 2011)
Whilst genetic factors are thought to contribute to the development of obsessive-compulsive disorder (OCD), the role of environmental factors in OCD is only beginning to be understood. In this article, we review the influence of stress-related factors in OCD. Overall, studies indicate that: patients with OCD frequently report stressful and traumatic life events before illness onset, although these rates do not seem to be significantly different from those described in other disorders; the association between OCD and post-traumatic stress disorder (PTSD) might result from symptom overlap, although cases of patients developing OCD after PTSD and showing obsessive-compulsive symptoms that were unrelated to trauma have been described fairly consistently; it is unclear whether patients with OCD and a history of stress-related factors (including stressful life events, traumatic life events or comorbid PTSD) may respond better or worse to the available treatments; and comorbid PTSD may modify the clinical expression of OCD-although controlled studies comparing pre-versus post-traumatic OCD patients are still unavailable. In conclusion, there is a growing evidence to suggest a role for stress-related factors in OCD. Although the available literature does not confirm the existence of a post-traumatic subtype of OCD, it does call for further systematic research into this topic. © 2011 Future Medicine Ltd.
Keywords: serotonin uptake inhibitor; agoraphobia; cognitive therapy; comorbidity; comparative study; disease association; disease course; disease severity; human; life event; major depression; obsessive compulsive disorder; outcome assessment; panic; posttraumatic stress disorder; priority journal; prognosis; review; social phobia; stressful life event; traumatic life event; trichotillomania; Yale Brown Obsessive Compulsive Scale